Types and Styles of Leadership in Islamic Boarding School Management (Tipe dan Gaya Kepemimpinan dalam Pengelolaan Pondok Pesantren) (Shautut Tarbiyah, 2023)
This study aims to analyze the types and styles of pondok leadership in the management of Islamic boarding schools. The data sources for this research are the Board of Directors of the Islamic Boarding School, the Board of Trustees of the Islamic Boarding School, and the Teachers of the Attarbiyatussakilah Islamic Boarding School, Kendari. This research was conducted qualitatively with a narrative approach. Data collection techniques were carried out through observation, interviews and documentation. Data analysis through the process of data reduction, data presentation and drawing conclusions. The results of the research show that: 1) In solving problems and making decisions in two ways, namely by way of deliberation and individual decision making. 2) In creating an atmosphere of good collaboration with subordinates, leaders instill a sense of mutual love and respect for each other, and never discriminate against their subordinates. 3) In accepting criticism, opinions and suggestions, leaders try to build a climate of openness.Kata Kunci:   Keywords: Type and style of leadership, Management of Islamic Boarding Schools